2016
DOI: 10.1186/s12882-015-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury induced by thrombotic microangiopathy in a patient with hemophagocytic lymphohistiocytosis

Abstract: BackgroundHemophagocytic lymphohistiocytosis (HLH) is a fatal clinical syndrome characterized by excessive immune activation and inflammation. It is frequently complicated by acute kidney injury (AKI) that often develops as acute tubular necrosis (ATN). Meanwhile, renal thrombotic microangiopathy (TMA) is a rare pathologic finding that mostly occurs in hemolytic uremic syndrome or thrombotic thrombocytopenic purpura. There are only few reports on TMA developing in patients with HLH. We present here a rare case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…We observed a high incidence of clinically significant complement-mediated thrombotic microangiopathy (TMA) associated with multi-organ injury in children and young adults with a diagnosis of HLH. TMA has not been previously associated with interferon gamma-driven diseases like HLH [26], but TMA has been reported as an iatrogenic therapylimiting side effect in patients receiving interferon alpha and beta therapy [27][28][29][30][31]. We hypothesized that high levels of interferon gamma in HLH might contribute directly to endothelial damage or injure endothelium through complement system activation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a high incidence of clinically significant complement-mediated thrombotic microangiopathy (TMA) associated with multi-organ injury in children and young adults with a diagnosis of HLH. TMA has not been previously associated with interferon gamma-driven diseases like HLH [26], but TMA has been reported as an iatrogenic therapylimiting side effect in patients receiving interferon alpha and beta therapy [27][28][29][30][31]. We hypothesized that high levels of interferon gamma in HLH might contribute directly to endothelial damage or injure endothelium through complement system activation.…”
Section: Discussionmentioning
confidence: 99%
“…There were three cases of clinically-diagnosed HLH complicated TMA which did not undergo biopsy (33,34). Bae et al (30) reported that TMA in HLH may occur with greater frequency than previously known, since diagnostic biopsies have rarely been performed in patients with HLH. If AKI occurred in patients with HLH, it is recommended that clinicians should also observe whether TMA is present in the patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…In TMA pathogenesis, endothelial injury is a key factor in the initiation of microemboli formation (35,36). The mononuclear-macrophage system is activated under the action of cytokines, releasing free radicals and proteolytic enzymes, resulting in endothelial cell damage and inflammatory reactions, thereby triggering TMA (30,33). Similarly, systemically-activated lymphocytes and macrophages and overproduction of highly elevated proinflammatory cytokines in the circulation such as IFN, TNF, IL-6 and macrophage-colony stimulating factor are pathogenetic characteristics of HLH (6,37).…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: Thrombotic microangiopathy (TMA) is a form of endothelial injury that has been reported as a complication of hemophagocytic lymphohistiocytosis (HLH) in adults . We report a case of Epstein–Barr virus (EBV)‐induced HLH and suspected TMA in a child.…”
Section: Patient's Laboratory Datamentioning
confidence: 99%